The performance of trading firms in the services sectors: Comparable evidence from four EU countries - Jože Damijan; Stefanie A. Haller; Ville Kaitila; Mika Maliranta; Emmanuel Milet; Matija Rojec; Daniel Mirza (The Research Institute of the Finnish Economy (ETLA), 2012)
We analyse common stylized facts of services firms engaged in trade in a comparative study across four EU member countries. We find that, though relatively less engaged in trade than manufacturing firms, services firms have similar traits. Services firms are more likely to import than to export. Their prevalent type of trade is trade in goods. The complexity of trade activities is increasing in firm size and productivity. Two-way traders outperform one-way traders. Services are more likely to be traded by firms already engaged in trade of goods. Changes in trading status by either adding another dimension of trade (imports, exports) or another type of product (goods, services) are infrequent and are associated with significant pre-switching premia. In contrast, learning effects from switching trading status are uncommon. This evidence points to significant fixed cost of being engaged in trade. Thus, the literature on heterogeneous firms is able to explain the sorting of firms into trading and non-trading firms in the services sectors as well.
Keywords: F14; F19; F23; 330; services sectors; exports; imports; trade in goods and services; trade premia